Usages du téléphone mobile et spatialité : Réflexions à partir du cas des femmes du Moungo central (Cameroun) - Jérémy Pasini (Cybergeo, 2023)
In Cameroon, trips undertaken by women are generally confined to a small area around their home and are closely monitored by men. In this context, we examine how the appropriation, adaptation, and use of mobile phones by women can help them gain more spatial control. To answer this question, we rely on the theory of the "arts of doing" (De Certeau, 1990). According to this theory, individuals benefit from a degree of autonomy in their usage of a technology. Our initial hypothesis is that women are capable of using and adapting the mobile phone to help them make spatial choices (choosing to phone people rather than travel, keeping a person at a distance by refusing to answer questions about localization, etc.). We therefore consider the mobile phone as a tool for "motility" (Kaufman and Jemelin, 2004), or even for 'spatiality' (Lussault, 2007). Based on data collected in Moungo (Cameroon) between 2014 and 2016, we show that the use of mobile phones gives women greater control over their use of space (making it easier to coordinate collective outings and easier to delay their return home, etc.). However, we also highlight that not all women benefit equally from phones. We suggest analysing the three factors which explain women's unequal ability to use mobile phones for their "spatiality": their financial capital, their level of education, and their age.